Design & Fabrication OF High-Performance GO-KART - Raghuvanshi, Ritu Raj; Bansod, Nakul; Chaporkar, Parag; Patel, Devendra; Chouhan, Deepesh; Panwar, Nandini; Bhadauriya, Aryan; Das, Madhav (Journal of Neonatal Surgery, 2025)
This report focuses on the design and innovation of a Go-Kart, with a particular emphasis on incorporating safety features. It outlines the objectives, assumptions, and calculations involved in the design process. The primary goal is to develop a safe, simple, and functional vehicle that adheres to sustainable principles, featuring a rigid and torsion-free frame. The final design integrates a combustion engine, ensuring ease of fabrication while prioritizing safety, performance, and overall reliability.